Validation of the Slovenian Intimate Violence and Traumatic Affect Scale (S-VITA) - Krohne, Nina (Violence against women, 2026)
This study addresses the scarcity of quantitative tools for assessing the mental health consequences of intimate partner violence on women, focusing on validating the Slovenian translation of the Intimate Violence and Traumatic Affect Scale (S-VITA). Using an online cross-sectional design, we surveyed a representative sample of 1,016 Slovenian women, with 275 experiencing intimate partner violence (IPV). Confirmatory factor analysis, performed on the IPV subsample, supported the proposed four-factor model (Fear, Terror, Guilt, and Shame) with strong internal consistency. The scale demonstrated robust construct and divergent, convergent, and cross-cultural validity. With compelling psychometric properties, we recommend its adoption by Slovenian professionals and researchers, suggesting its applicability in diverse linguistic contexts.